2014
DOI: 10.1097/qai.0b013e3182a97c17
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Wave Velocity as Index of Arterial Stiffness in HIV-Infected Patients Compared With a Healthy Population

Abstract: Virologically suppressed HIV-infected patients showed similar arterial elasticity to non-HIV-infected patients. HIV-related conditions were not associated with arterial stiffness, probably because of the good immunologic and virological status of this group. However, high diastolic pressure at the time of PWV and high levels of triglycerides were associated risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 37 publications
3
36
0
Order By: Relevance
“…The cf-PWV values observed are similar to the reference values for patients aged 40-49 years [optimal 7.0 (4.5-9.6) m/s and normal 7.5 (5.1-10.0) m/s] [22]. Our results are in line with previous studies that found no differences in aortic stiffness between HIV-infected and HIV-uninfected groups [12,13]. Participants in these studies presented similar demographic and clinical characteristics to those in our study, including age above 40 years and higher prevalence of hypertension and dyslipidemia among the HIV-infected individuals.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…The cf-PWV values observed are similar to the reference values for patients aged 40-49 years [optimal 7.0 (4.5-9.6) m/s and normal 7.5 (5.1-10.0) m/s] [22]. Our results are in line with previous studies that found no differences in aortic stiffness between HIV-infected and HIV-uninfected groups [12,13]. Participants in these studies presented similar demographic and clinical characteristics to those in our study, including age above 40 years and higher prevalence of hypertension and dyslipidemia among the HIV-infected individuals.…”
Section: Discussionsupporting
confidence: 95%
“…Conversely, several other studies found increased aortic stiffness in HIV-infected individuals [9][10][11]. Such discrepancies may be because of differences in study population characteristics, notably cART use, immunologic status, cardiovascular risk level, and variations in the methods used to evaluate aortic stiffness, particularly cardiac magnetic resonance [11], SphygmoCor [9,10,15,17,18] and Complior [12][13][14]16]. Our cross-sectional study provides additional information by observing that, among HIV-infected individuals, aortic stiffness is associated with both nadir CD4 þ T-cell count, a marker of past profound immunodeficiency, and traditional cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Aortic PWV reference values represent reliable estimates according to age and BP, allowing comparison with carotid-femoral PWV in our study population. Consistent with our results, similar values of aortic PWV in HIVinfected patients in the HAART era compared to uninfected individuals were recently described [18,34]. Age, MAP and diabetic status were independent factors associated with increased aortic PWV in our study, with a strong correlation with age and MAP, findings highly consistent with the literature [33,35].…”
Section: Central Arterial Parameters and Hiv Infectionsupporting
confidence: 83%
“…Central augmentation index (AIx), which is considered a transit time-dependent marker of intensity of arterial wave reflections, and pulse pressure (PP) amplification, also bring independent predictive value for CV events and mortality [16,17]. However, such parameters may be difficult to interpret in HIVinfected patients because the association between HIV infection and greater arterial stiffness or wave reflections may be no longer significant after adjustment for classical risk factors, especially smoking and hypertension [18].…”
Section: Introductionmentioning
confidence: 99%